Atypical melanocytic lesions: a historical overview - Manchi, Melissa; Canzonieri, Vincenzo (Polish Journal of Pathology, 2019)
The distinction between atypical Spitz lesions, conventional melanocytic nevi including Spitz nevi, and malignant melanomas may be difficult in some cases or may even be impossible. The histological assessment of these lesions is necessary to ensure correct diagnosis and treatment. Nevertheless, pathologists may be subject to suboptimal concordance in the diagnosis of some atypical lesions. In literature, certain atypical lesions have been defined differently: the terms atypical and metastasising Spitz tumour, malignant Spitz nevus, borderline and intermediate melanocytic tumour, melanocytic tumour of uncertain malignant potential MELTUMP, and low-grade malignant melanoma have been introduced to designate this heterogeneous group of pathological entities and variants. This review focuses on some issues concerning the historical background, diagnostic state-of-the-art, evolution, and classification of these complicated lesions.